Morphology engineering in monolayer MoS2‐WS2 lateral heterostructures - Zhou, Jiadong (2019)
In recent years, heterostructures formed in transition metal dichalcogenides (TMDs) have attracted significant attention due to their unique physical properties beyond the individual components. Atomically thin TMD heterostructures, such as MoS2‐WS2, MoS2‐MoSe2, MoS2‐WSe2, and WSe2‐WS2, are synthesized so far via chemical vapor deposition (CVD) method. Engineering the morphology of domains including size and shape, however, still remains challenging. Here, a one‐step CVD strategy on the morphology engineering of MoS2 and WS2 domains within the monolayer MoS2‐WS2 lateral heterostructures through controlling the weight ratio of precursors, MoO3 and WO3, as well as tuning the reaction temperature is reported. Not only can the size ratio in terms of area between WS2 and MoS2 domains be easily controlled from less than 1 to more than 20, but also the overall heterostructure size can be tuned from several to hundreds of micrometers. Intriguingly, the quantum well structure, a WS2 stripe embedded in the MoS2 matrix, is also observed in the as‐synthesized heterostructures, offering opportunities to study quantum confinement effects and quantum well applications. This approach paves the way for the large‐scale fabrication of MoS2‐WS2 lateral heterostructures with controllable domain morphology, and shall be readily extended to morphology engineering of other TMD heterostructures.